A Comprehensive Overview Of Host Defense Mechanisms In Microbial Infections: Significance Of Innate And Adaptive Immunity In Body For Human Health (The Review of Diabetic Studies, 2025)
The immune system is a complex and an extremely flexible line of defense that is simply critical in the protection of an organism against diseases. It is normally classified into two key categories namely innate and adaptive immunity. Innate immunity is the first line of defense comprising of timely actions against infections and non-specific responses with the aid of epithelial and mucosa barriers, inflammatory molecules, and cells, namely macrophages, neutrophils, and natural killer (NK) cells. The same cells perceive and destroy infectious agents and trigger the cascade of inflammation at the same time and other immune pathways. The difference in contrast is adaptive immune which is characterized by antigen-specificity and immunological memory. The T and B lymphocytes have specificity to antigens and the differentiation T cells into the helper or the T cytotoxic cells, and B cells produce the antibodies that neutralize pathogens and activate the complement response. Immunological memory allows the adaptive system to elicit a faster and better response on repeated exposure to the pathogen previously challenged. An integrated functional immune response is enabled by the synergistic fusing of both innate and adaptive immunity. Also, the microbiome present within individuals has a shaping effect on systemic and local immune activities. These immune components can only be completely understood to accurately improve therapeutic measures in vaccination, immunotherapy and in the treatment of autoimmune diseases. This review therefore outlines the principle functions of immunity and the key importance of the innate and adaptive systems in maintaining health and overcome infectious challenges.